Inflation expectations and consumer sentiments of the Urals population - Aleksey A. Korikov; Konstantin P. Yurchenko (Journal of New Economy, 2024)
In recent decades, central banks of an increasing number of countries have been using the inflation targeting regime in their monetary policy, since it has proven to be an effective tool for balancing economic growth and inflation. In countries with the regional heterogeneity, local manifestations of inflation may differ significantly, which entails a shift in inflation expectations and their unequal impact on actual dynamics of prices in the future. The article explores the determinants of inflation expectations in Ural regions of Russia. The methodological basis of the study includes monetary concepts developed primarily within the framework of the new Keynesian theory and linking monetary policy with the assessments of inflation expectations. The study uses methods of statistical processing of the data collected during two rounds of monitoring of the population’s inflation expectations. The evidence of the study comes from the surveys conducted on a sample of 2,976 respondents. The study reveals regional, social and allocative heterogeneity in the perception of dynamics of prices and the formation of inflationary expectations. The results of the study contribute to understanding the nature of inflation expectations using the case of the Urals population and can become a basis for developing targeted communication measures aimed at bringing inflation closer to the target.